FORECASTING TOMATO PRODUCTION UNDER CLIMATE VARIABILITY IN PAKISTAN - M. K. Bashir; A. U. Malik; M. U. Farrukh; S. Hameed; M. A. Kamran; K. Ziaf (Journal of Animal and Plant Sciences, 2022)
Pakistan contributes the lowest to per capita greenhouse gas (GHG) emissions but is among the five worst affected countries in the world. This paper forecasts tomato production under climate variability in Pakistan. Time series data were collected from Government of Pakistan (GOP), Food and Agriculture Organization (FAO) and World Bank's online sources. Both quantitative and qualitative techniques were applied to analyze the data. For quantitative analyses, dynamic forecasting techniques were used, and qualitative analyses were carried out using the rapid appraisal method. The results concluded that temperature shocks have adverse dynamics on tomato production as well as prices. An ambiguous role of rainfall was found i.e., in some areas it had positive impact while in other areas had negative impacts. Several issues were identified including limited area of production, low yields, pests and disease stresses, labor shortage, poor water management and lack of modern information. It is suggested that value chain industry of tomato must be developed in tomato growing areas Furthermore, the access of farmers to reliable information about weather dynamics must be ensured.
Keywords: Climate variability; dynamic forecasting; Pakistan; price volatility; tomato production